Extending social protection to persons with disabilities: Exploring the accessibility and the impact of the Disability Fund on the lives of persons with disabilities in Ghana. (December 2019) - Opoku, Maxwell Peprah; Nketsia, William; Agyei-Okyere, Elvis; Mprah, Wisdom Kwadwo
In many low-income countries, persons with disabilities are consistently denied access to essential services, contributing to a high incidence of poverty among them. The Goal 1 of the Sustainable Development Goals (SDGs) exhorts countries to develop appropriate social protection to serve as a springboard to alleviate poverty among all persons. The government of Ghana has introduced Disability Fund to provide one-off financial support to persons with disabilities through its decentralised political units. This is to enable persons with disability to participate in socio-economic activities. However, after a decade of the establishment of the fund, anecdotal evidence still shows that many persons with disabilities continue to live in deplorable conditions. Therefore, the main aim of this qualitative study was to explore the beneficial impact of the fund on the lives of persons with disabilities in Ghana. A semi-structured interview guide was used to collect data from 48 participants, comprising 20 males and 28 females with disabilities. The narratives from the participants revealed that only a few were able to access the fund. In their quest to access the fund, participants encountered barriers, such as lack of information, delays in disbursement and insufficient funds. The findings underscore the need for re-evaluation of the administration of Disability Fund and its disbursement processes. The implications of the findings for policy reform are extensively discussed.